2013
DOI: 10.7196/samj.6077
|View full text |Cite
|
Sign up to set email alerts
|

Risk of nevirapine-associated Stevens-Johnson syndrome among HIV-infected pregnant women: The Medunsa National Pharmacovigilance Centre, 2007 - 2012

Abstract: Background. Stevens-Johnson syndrome (SJS) is an acute life-threatening condition often elicited by drugs. The government's indecisiveness in deciding to stop the use of nevirapine (NVP) in HIV-infected pregnant women owing to the increase of SJS among this population group in South Africa prompted this investigation. Objectives. To investigate if pregnancy is a risk factor for SJS among HIV-infected women taking NVP-containing regimens and registered within the Medunsa National Pharmacovigilance Centre databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…Almost all of the published data, mainly case reports, has been on SJS/TEN. It is not clear if pregnancy itself predisposes the mother to SCAR although one small study in South Africa suggested that pregnancy is a risk factor for SJS in HIV-infected women taking nevirapine (123). There are a handful of published reports of maternal SJS/TEN affecting the unborn fetus (124).…”
Section: Managementmentioning
confidence: 99%
“…Almost all of the published data, mainly case reports, has been on SJS/TEN. It is not clear if pregnancy itself predisposes the mother to SCAR although one small study in South Africa suggested that pregnancy is a risk factor for SJS in HIV-infected women taking nevirapine (123). There are a handful of published reports of maternal SJS/TEN affecting the unborn fetus (124).…”
Section: Managementmentioning
confidence: 99%
“…Other causes of SJS and TEN include certain infections [15]. For unclear reasons, it was found that patients with human immune deficiency virus (HIV) have higher risk of developing SJS and TEN compared to un-infected people [7, 1621]. Other infections such as Mycoplasma pneumoniae infections and herpes simplex viral infections were linked to SJS and TEN even without previous exposure to medications [2227].…”
Section: Introductionmentioning
confidence: 99%
“…Nevirapine toxicity is common [6,7]. Control studies have reported that pregnancy is a risk factor for TEN/SJS when HIV-positive women are treated with a combination of nevirapine with an odds ratio of 14.28 (p=0.006), a 95% confidence interval (1.54-131.82) [8]. All women had taken antiretroviral triple therapy as part of mother-child prevention of HIV transmission with an average CD4 cell count at 416/ mm 3 , viral load was not available.…”
Section: Discussionmentioning
confidence: 99%